Effect of altitude on thermal responses of Liolaemus pictus argentinus in Argentina - Gutiérrez, Joel A. (2010)
Reptiles that live in cooler environments hibernate longer and, when active, limit daily activity times, allocate more time and energy toward thermoregulation and consequently experience life-history constraints such as reduced fecundity and supra-annual reproductive cycles. This pattern becomes more extreme with increasing latitude and altitude. We compared the thermal biology of two populations of Liolaemus pictus argentinus living at two altitudes (771 and ~1700 m asl). Environmental, microenvironmental, and operative temperatures were studied in order to describe the capture sites, sources of heat, and availability of microenvironments appropriate for thermoregulation. The body temperatures of L. p. argentinus at capture (Tb), and the preferred temperatures in the laboratory (Tp) were recorded and integrated with operative temperatures to calculate the effectiveness of thermoregulation. The high-altitude population was found to have a lower mean Tb (29 ºC compared to 33 ºC), while the Tp values for both populations were similar (36.7 ºC). The analysis of operative temperatures and Tb in relation to Tp showed that L. p. argentinus behaves as a moderate thermoregulator at high altitude and as a poor thermoregulator at the low-altitude site probably due in part to the avoidance of predation risk.